Enhancement of Solar Cell Modeling with MPPT Command Practice with an Electronic Edge Filter - Saad, S. (Engineering, Technology & Applied Science Research, 2021)
A new photovoltaic cell modeling based on an electronically tunable edge filter is presented in this paper. The new model is subjected to temperature, illumination, and resistance variations. In addition, an MPPT (Maximum Power Point Tracker) command was exposed with a calculation algorithm based on a microcontroller card that used the behavior of an electronically tunable edge filter. The results confirm those published in the literature, showing the influence of the position of the leakage variation in our model, which can give more power. The simulation results show that the proposed command is efficient to determine the MPP point.